Group-specific 16S rRNA hybridization probes to describe natural communities of methanogens. - Raskin, L (1994)
Eight oligonucleotides which are complementary to conserved tracts of 16S rRNA from phylogenetically defined groups of methanogens were designed and characterized for use as hybridization probes for studies in environmental and determinative microbiology. The target-group specificity and temperature of dissociation for each probe were characterized. In general, the probes were very specific for the target methanogens and did not hybridize to the rRNAs of nontarget methanogens. Together, the eight probes circumscribe methanogens now represented in pure culture (with the exception of members of the family Methanothermaceae). Three probes are order specific; two identify members of the order Methanobacteriales, and one is specific for the order Methanococcales. The fourth probe encompasses three families belonging to the order Methanomicrobiales, the third order within the current classification. The fifth probe is specific for the remaining family within this order (Methanosarcinaceae). Three additional probes encompass different genera within the Methanosarcinaceae.